Pancreatic cancer prognosis is predicted by an ATAC-array technology for assessing chromatin accessibility - S. Dhara (Nature Portfolio, 2021)
ATAC-seq allows for the investigation of chromatin accessibility, a feature which can have important implications for gene regulation. Here the authors present ATAC-array to assess accessibility in human tumours and based on this predict disease prognosis.